Production and consumption pattern of livestock products in Meghalaya and its implications in development of market strategies for the state producers - TRIPATHI, A K; YUMNAM, A; SINGH, N U; ROY, A; DANGI, D; DEBROY, P; SINHA, P K (The Indian Journal of Animal Sciences, 2019)
To find out the trend in production and consumption of livestock products in Meghalaya and explore the means and ways to plan an efficient and proper market accordingly, the study was conducted using both secondary and primary sources of data. The clear cut objectives were to examine and analyse the growth in livestock population in Meghalaya and to analyse the consumption pattern of livestock products. Compound annual growth rates (CAGRs) in livestock population during nine inter-census periods were positive for cattle, pig and poultry; negative growth rates were observed during few periods in case of buffalo, sheep, goat and horses and ponies; sheep population mostly showed negative growth rate as sheep is reared mainly for meat purpose and the meat is not as popular as beef or pork. Milk, egg, mutton and chicken are still luxury items in the rural region; egg and chicken are items of luxury in urban regions whereas fish consumption was relatively income inelastic in both rural and urban regions. Thrust can be made in the processing of milk into different milk products and popularization of sheep rearing focusing on rearing for wool rather than meat.